2001
DOI: 10.1097/00005537-200102000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Excision of the Preauricular Sinus: A Comparison of Two Surgical Techniques

Abstract: The supra-auricular approach for excision of a preauricular sinus has a statistically lower recurrence rate in comparison to the standard technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 10 publications
3
46
1
4
Order By: Relevance
“…The present study findings concurred with ElAassar et al 6 where only one case showed recurrence with supra-auricular approach and the difference was found significant statistically. Similar findings were found in a study by Lam et al, 7 where supra-auricular approach was found to have least recurrence compared to simple sinusectomy.…”
Section: Discussionsupporting
confidence: 91%
“…The present study findings concurred with ElAassar et al 6 where only one case showed recurrence with supra-auricular approach and the difference was found significant statistically. Similar findings were found in a study by Lam et al, 7 where supra-auricular approach was found to have least recurrence compared to simple sinusectomy.…”
Section: Discussionsupporting
confidence: 91%
“…A more radical supra-auricular approach (Wide local excision) was made by Prasad et al in 1990 [9] and by Lam et al in 2001 [10]. Based on these reports, the supra-auricular approach has a lower recurrence rate 5% (of 21) vs. 42% (of 12) [9] and 3.7% (of 27) vs. 32% (of 25) [10]. And our series had zero recurrence rate in 34 cases with a follow up of 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…insertion of a probe or instillation of Methylene blue [5,6], expanding the area of resection [4,7,8] or even interposition of the temporoparietal fascia [9].…”
Section: Discussionmentioning
confidence: 99%